DISCOURSE SEMANTIC ANALYSIS ON STUNDENTS RECOUNT TEXT OF SMUK ST. IGNATIUS LOYOLA - Hieronimus C. Darong (Unika Santu Paulus Ruteng, 2016)
Discourse Semantic Analysis on the Students’ Recount Text of SMUK St. Ignatius Loyola. This study aims at describing and analyzing the register category, namely field, tenor, and mode of the texts. The object of the research was fifteen recount texts from which the three register categories were analyzed. The texts were modified into clauses which will, in turn, be analyzed in accordance with the goal of analysis, that is, to investigate the register category of field, tenor, and mode. The steps of analysis were based on the concept of Systemic Functional Linguistics (SFL).